The Legal Personality of the European Union – Between the Maastricht Treaty and the Draft Treaty Establising a Constitution for Europe – Reality and Pperspectives - Octavian Gabriel Pascu; Caius Tudor Luminosu (Romanian Journal of European Affairs, 2006)
The scope of the present article is to present an overview of the prevailing and accepted opinion on the legal personality of the European Union. The starting point of the presentation is the analysis of the structural differences between the EU and the European Communities. Then followed by the institutional delimitation and the differentiation of these bodies within the European Construct with regard to actual European Law. After a brief presentation of the legal nature of the EU and its lack of legal personality and legal capacity, a scrutiny of the international law requirements to international law subjectivity of the EU is performed with the same result, but this time on international law level, denying the state character of the Union. This also represents the prevailing opinion in German literature, denying the existence of a legal personality of the EU on a public and international law level with respect to the actual European law. Further, we undertake an analysis on the international law effects of the lacking legal capacity of the Union. This is followed by a short exposition of the effects on European institutions of the awarding of legal personality to the EU. In the final part of the present article the focus is on the new European Constitution, still to be adopted by the member states, which expressly provides the fact that the Union is granted the legal personality and its implication on the present situation in the literature.